Arab Women’s Experiences of Careers in Management - CHAYA, SHIREEN N. (2018)
This thesis explores the experiences and decisions of young Arab women as they pursue and advance their careers in management or opt out. The main research questions on Arab women’s management careers include how they perceive their experiences in organisations, the key elements that contribute to their decision to leave their management career or stay, how they perceive upward mobility in management careers, and the way in which their experiences are qualitatively changed by the overlapping of multiple layers of identity at particular points of intersection. The thesis draws on discourses of gender, intersectionality, and sustainability situated in the paradoxical context of the region in which Arab women, while young and educated many are not working in management or unemployed. The thesis’s aim and research questions were explored through hermeneutic phenomenology via the semi-structured life world interview drawing on a sample of 56 women from 17 Arab countries, between the ages of 24-40, holding degrees in management, who are currently working or worked a minimum of 3 years before quitting. An Arab woman was defined as someone for whom both parents are Arab, has lived in an Arab country for at least ten years, obtained at least one degree in a higher education institution in an Arab country, and has previously or currently works in an Arab country for a minimum of 3 years. Several themes emerged that described women’s management career experiences specifically from the perspective of their social identities the combination of which produce private and public scripts with multiple intersections qualitatively changing their experiences. Shared among their experiences is the way in which these intersections situated them in what they perceived to be places of “empowerment” or “disempowerment” expressed in the ability to make decisions and seek alternatives as they underwent expected role-performance tensions during daily “power” episodes with multiple actors (especially managers, colleagues, spouses and other family members). Thus, the power framework of Arab women’s management careers tells of an active participant and a knowledgeable agent aware of the importance of balancing multiple arenas of power. Based on this argument and interpretation the thesis makes recommendations on how to transform various elements such that women experience more equitable and empowering decision-making options that encourage them to remain in their careers as well as move upwards facilitated by cultural and policy changes in universities, organizations, and governments.